The effect of the counselor's intolerance on the expressed level of empathy under varying conditions of ethnicity - Teta, Diana C. (University of Ottawa (Canada), 1976)
Abstract not available.
Keywords: Psychology, Counseling.; Sociology, Ethnic and Racial Studies.